Interviewing principles and practices - Stewart, Charles J.; Cash, William B. Jr (McGraw-Hill Education, 2014)
"This fourteenth edition of Interviewing: Principles and Practices continues a tradition started with the first edition that appeared in 1974. It focuses on the fundamental principles applicable to all forms of interviewing and to seven specific types of interviewing while incorporating the latest in research, interpersonal communication theory, the uses of technology and social media, the role of ethics in interviewing, and EEO laws that affect employment and performance interviews. While we have included recent research findings and developments, we continue the emphasis on building the interviewing skills of both interviewers and interviewees. Several chapters address the increasing diversity in the United States and our involvement in the global village as they impact the interviews in which we take part.We have continued our quest to make each edition more reader-friendly by tightening up the writing style, eliminating unnecessary materials and redundancies, making explanations and definitions more precise, reducing the frequency of lists and using a variety of print types to call attention to important words, terms, and concepts. Portions of several chapters have been restructured to take readers through each in a clearer and more natural progression. A list of objectives now appears at the start of each chapter to orient students to the major topics and purposes of the chapter. Notes in the margins provide guidelines, cautions, and observations. Lists of key terms appear at the end of each chapter, and a glossary of important terms is provided at the end of the book"--Provided by publisher.